2017
DOI: 10.1111/gcb.13863
|View full text |Cite
|
Sign up to set email alerts
|

Improving predictions of tropical forest response to climate change through integration of field studies and ecosystem modeling

Abstract: Tropical forests play a critical role in carbon and water cycles at a global scale. Rapid climate change is anticipated in tropical regions over the coming decades and, under a warmer and drier climate, tropical forests are likely to be net sources of carbon rather than sinks. However, our understanding of tropical forest response and feedback to climate change is very limited. Efforts to model climate change impacts on carbon fluxes in tropical forests have not reached a consensus. Here, we use the Ecosystem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 134 publications
2
60
0
Order By: Relevance
“…Perhaps increased flowering and fruiting can be expected in the LFDP forest community, caused by more frequent ENSO events through the 21st century. This prediction must be tempered by the possibility that climatically driven shifts in Puerto Rico's life zones (Henereh et al 2016) may cause biotic attrition (Colwell et al 2008) of the forest community that may disrupt forest productivity and reproduction in ways more profound than changes in ENSO (see Feng et al 2018). Meanwhile, the frequency of hurricanes is expected to decrease over time as global climate warms through the remainder of the century, but with increased numbers of Category 4 and 5 storms as SSTs become warmer (Knutson et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps increased flowering and fruiting can be expected in the LFDP forest community, caused by more frequent ENSO events through the 21st century. This prediction must be tempered by the possibility that climatically driven shifts in Puerto Rico's life zones (Henereh et al 2016) may cause biotic attrition (Colwell et al 2008) of the forest community that may disrupt forest productivity and reproduction in ways more profound than changes in ENSO (see Feng et al 2018). Meanwhile, the frequency of hurricanes is expected to decrease over time as global climate warms through the remainder of the century, but with increased numbers of Category 4 and 5 storms as SSTs become warmer (Knutson et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The number of days with 5 mm of rain is expected to decrease, causing an increase in seasonality in Caribbean montane wet forests (Waide et al 2013). A recent parameterization of the Ecosystem Demography model (Feng et al 2018) for Puerto Rican wet forest indicated that net ecosystem productivity of wet forest could reach 0 within 20 yr if decreased precipitation and increased temperatures occur as projected. Additionally, the frequency of intense hurricanes (categories 4 and 5 on the Saffir-Simpson scale) may increase with global warming (Knutson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, forest regeneration rates are likely to be affected by future climatic changes, with India projected to see increases in both temperature and precipitation (Gosling et al 2011). The integrated impacts of this on the regeneration of moist sub-tropical and montane landscapes prevalent in Northeast India and in turn on carbon pricing is uncertain, although warmer and wetter conditions could improve the rate of forest recovery and total carbon stocking further reducing breakeven carbon prices (Poorter et al 2016, Feng et al 2018.…”
Section: Figurementioning
confidence: 99%
“…Henareh et al [21], Gould et al [22], Feng at al. [23], Jennings et al [24], Van Beusekom et al [25,26] Monitoring of changes in biodiversity Campos-Cerqueira et al [27], Wunderle and Arendt [28], González et al [29], Heartsill-Scalley and González [30] Understanding novelty Lugo and Erickson [31] Attention to urban environments and their functioning Muñoz-Erickson et al [32] A social-ecological-technological focus Lugo and Alayón [33], Lugo [34] Fomenting collaboration among many sectors of society González and Heartsill-Scalley [35] Development of novel policies for effective governance McGinley [36], Rudel [37] Institutional improvement M. Rains [38] * Manuscripts are part of this Special Issue or are recent products of the Institute's program.…”
Section: Element Of Research or Action Contributed Manuscripts*mentioning
confidence: 99%